Edaphic specialization in relation to termite mounds in Katanga (DR Congo): A reciprocal transplant experiment with congeneric tree species. (18th September 2018) - Cuma Mushagalusa, Fidèle; Bauman, David; Mujinya Bazirake, Basile; Mleci, Yona; Kalenga, Mpibwe; Ngoy Shutcha, Mylor; Meerts, Pierre
Abstract: Question: Do termitophilous and non‐termitophilous trees of dry tropical woodlands show local adaptation? Location: Region of Lubumbashi, Upper Katanga, DR Congo. Methods: Three pairs of congeneric tree species showing strict edaphic specialization with respect to termite mounds, Combretum molle (termitophilous, T)/ C. collinum (non‐termitophilous, NT); Strychnos potatorum (T)/ S. spinosa (NT), Ziziphus mucronata (T)/ Z. abyssinica (NT), were used in a reciprocal transplant experiment in situ. Seedlings were reciprocally transplanted on termite mounds and in the surrounding matrix in a miombo woodland. Growth (height and number of leaves) and survival were monitored for 30 months. Soil physical and chemical properties, and available water, were assessed on and off mounds. Results: Growth was little affected by habitat; only one species showed better growth in its home habitat ( S. spinosa in the matrix). Survival was strongly affected by habitat, in opposite directions consistent with species' habitat specialization. Termitophilous species experienced a very high mortality rate in the matrix, especially during the dry season. Available water content was higher in termite mound soil than in the matrix soil. Conclusions: Termitophilous and non‐termitophilous tree species show local adaptation at the seedling stage, expressed mostly as different patterns of mortality in the dry season. The results point to water supply as a critical factor in the edaphic specialization of termitophilous species. In contrast, the higher mortality of non‐termitophilous species on termite mounds is not explained by water stress. Abstract : Monitoring of seedling survival on a termite mound at Mikembo Sanctuary (DR Congo).